Living waters : reading the rivers of the lower Great Lakes - Wooster, Margaret (Excelsior Editions/State University of New York Press, 2009)
"In Living Waters, Margaret Wooster canoes, portages, camps beside, and wades into eight Great Lakes watersheds across New York and Quebec, returning with her pockets full of original stories from these beautiful, boggy, and prehistoric waterways. From the history of hydropower development on the Niagara River to the search for a wizard's cave in the Zoar Valley, from a portrait of an urban creek in Buffalo, to the origins and demise of New France on the St. Lawrence, Living Waters offers a fascinating, first-person exploration of the rivers that impact our world's largest freshwater ecosystem."--Jacket